1899
DOI: 10.5962/bhl.title.46340
|View full text |Cite
|
Sign up to set email alerts
|

The forests of the United States

Abstract: The area of woodland has been obtained from the census of 1880. Sq. milea. Total land area 9 Q05 Woodland in farms 2 000 Woodland not in farms 3 200 Total woodland 5 200 Percentage of land area, 58. VERMONT.The area of woodland has been obtained from the census of 1880.Sq. miles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1950
1950
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…One or two of these predictions have by accident hit very near the truth, as made known by later censuses, but all have been finally wide of the mark" [15]. Moreover these estimates were all wide of the mark because they assumed a much larger increase in population than actually took place.…”
Section: Early Forecastsmentioning
confidence: 94%
“…One or two of these predictions have by accident hit very near the truth, as made known by later censuses, but all have been finally wide of the mark" [15]. Moreover these estimates were all wide of the mark because they assumed a much larger increase in population than actually took place.…”
Section: Early Forecastsmentioning
confidence: 94%
“…Therefore, for the historical condition along nonfloodplain channels, we assumed mature dense conifer stands with a site potential tree height of 52 m. This height is based on growth trajectories in McArdle et al (1930), descriptions found in Gannett (1899), and the average tree height at six present-day old-growth sites in the Stillaguamish River Basin (48 m; M. Pollock, unpublished data, 1998). For mixed forests along floodplain channels, we used a typical tree height for mature hardwoods of 30.5 m. The value is meant to JOURNAL OF THE AMERICAN WATER RESOURCES ASSOCIATION represent an approximate weighted average of red alder (~30 m), black cottonwood (~40 m), and willow (~6 m).…”
Section: Reference Condition For Riparian Analysismentioning
confidence: 99%
“…Situated in the Chihuahuan Desert, the Sierra Vieja (also referred to as the Tierra Vieja, Vieja Mountains: Gannett 1904; Sierra Vieja Range: Jameson and Flury 1949, Philips and Thornton 1949; Sierra Tierra Viejas: York 1949) is a low-elevation mountain range (1500–1900 m) located north and east of the Rio Grande in western Jeff Davis and Presidio counties, Texas, USA that is approximately 65 km in length and primarily composed of igneous rock (York 1949). The Sierra Vieja serve as an important barrier between the Rio Grande Plain to the west and the Valentine Plain to the east, with its steep, incised canyons providing protection and habitat in an otherwise open terrain.…”
Section: Introductionmentioning
confidence: 99%